2003
DOI: 10.1677/joe.0.1790427
|View full text |Cite
|
Sign up to set email alerts
|

The response of the hepatic insulin-like growth factor system to growth hormone and dexamethasone in calves

Abstract: Glucocorticoids inhibit postnatal growth and yet can stimulate the somatotropic axis around birth. The aim of the present study was to investigate the effects of dexamethasone on the somatotropic axis and on the responses of the insulin-like growth factor (IGF) system to growth hormone treatment in calves. Calves (n=24) were randomly divided into four groups. Group DX was injected with dexamethasone (30 µg/kg body weight per day), group GH was injected with 500 mg slow-release bovine growth hormone at 14-day i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…The decreased expression of IGFBP-5 following Dex treatment is similar to previous reports that glucocorticoids, such as Dex, have growth suppressing effects, inhibit the somatotropic axis, and long-term treatment leads to bone loss and osteoporosis [31][32][33][34]. Our data are similar to previous observations that Dex treatment decreased expression of IGF-I, IGFBP-3, and IGFBP-5, stimulatory factors, and increased expression of IGFBP-4, an inhibitory factor, in human osteoblast-like cells and decreased IGFBP-5 expression in preosteoblastic human bone marrow stromal cells [35,36].…”
Section: Coordinated Expression Of Igfbp-5 Fhl-2 and Adam-9 In Respsupporting
confidence: 88%
“…The decreased expression of IGFBP-5 following Dex treatment is similar to previous reports that glucocorticoids, such as Dex, have growth suppressing effects, inhibit the somatotropic axis, and long-term treatment leads to bone loss and osteoporosis [31][32][33][34]. Our data are similar to previous observations that Dex treatment decreased expression of IGF-I, IGFBP-3, and IGFBP-5, stimulatory factors, and increased expression of IGFBP-4, an inhibitory factor, in human osteoblast-like cells and decreased IGFBP-5 expression in preosteoblastic human bone marrow stromal cells [35,36].…”
Section: Coordinated Expression Of Igfbp-5 Fhl-2 and Adam-9 In Respsupporting
confidence: 88%
“…Consistent with this, this study showed that GH injection increased mRNA expression of IGF1 and ALS in both the cows fed concentrates and the cows fed hay. GH has been shown to stimulate liver expression of IGFBP3 mRNA in rats (Albiston & Herington 1992, Domene et al 1993, Scharf et al 1996, sheep (Bassett et al 1998), and pigs (Dunaiski et al 1999), but not in cattle (Hammon et al 2003, Radcliff et al 2004. This study showed that GH injection increased IGFBP3 mRNA expression in the liver of cows fed hay, but not in those fed concentrates.…”
Section: Discussionmentioning
confidence: 65%
“…Time changes in the plasma IGFBP-3 concentration were small, and surprisingly, no feeding effect was observed during the intensive MR-feeding period. Previous studies have shown an increase in plasma IGFBP-3 in calves with age [79,80] and MR-feeding intensity [32], and plasma IGFBP-3 normally follows plasma IGF-I, because IGFBP-3, together with an acid-labile subunit, binds most of the IGF-I in circulation and therefore correlates well with IGF-I [28,37,38]. In addition, the plasma IGFBP-3 inversely correlates with IGFBP-2 during growth [29,37], which was also not observed in the present study.…”
Section: Discussionmentioning
confidence: 99%